Plant Watering Autonomous Mobile Robot - Hema Nagaraja; Reema Aswani; Monisha Malik (Institute of Advanced Engineering and Science, 2012)
Now days, due to busy routine life, people forget to water their plants. In this paper, we present a completely autonomous and a cost-effective system for watering indoor potted plants placed on an even surface. The system comprises of a mobile robot and a temperature-humidity sensing module. The system is fully adaptive to any environment and takes into account the watering needs of the plants using the temperature-humidity sensing module. The paper describes the hardware architecture of the fully automated watering system, which uses wireless communication to communicate between the mobile robot and the sensing module. This gardening robot is completely portable and is equipped with a Radio Frequency Identification (RFID) module, a microcontroller, an on-board water reservoir and an attached water pump. It is capable of sensing the watering needs of the plants, locating them and finally watering them autonomously without any human intervention. Mobilization of the robot to the potted plant is achieved by using a predefined path. For identification, an RFID tag is attached to each potted plant. The paper also discusses the detailed implementation of the system supported with complete circuitry. Finally, the paper concludes with system performance including the analysis of the water carrying capacity and time requirements to water a set of plants.DOI: http://dx.doi.org/10.11591/ijra.v1i3.1305